(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
To obtain high-quality ceramics, it is necessary to grind the raw material and obtain a fine-dispersed structure. This problem was solved by converting aluminum waste and its alloys into nanostructured aluminum hydroxide, which allows obtaining ceramics with high properties. The heat treatment regime of the original aluminum hydroxide in air (1350 0C, 1 hour) was developed to convert it into aluminum oxide (γ and α - modifications), ensuring the preservation of high activity of the aluminum oxide powder for heating and bonding.